The Watford low anterior resection syndrome pathway for pre- and post-stoma reversal patients. (2nd September 2019) - Sumner, Deborah; Collins, Brigitte
Abstract : There is increasing awareness of the high incidence of bowel dysfunction experienced by patients after sphincter-preserving rectal resection, termed low anterior resection syndrome (LARS); there remains no agreement on effective methods of treatment or effective management strategies. In West Hertfordshire Hospitals NHS Trust, there were no set protocols in place prior to the development of a nurse-led LARS clinic, which has ensured that all patients undergoing anterior resection surgery are monitored, encouraged and empowered to take an active role in their own care. While being the first point of contact for these patients, the nurse works as part of a wider multidisciplinary team (MDT) and the surgical consultants continue to have overall responsibility for patient care. The Watford LARS pathway is a guide with a method of how best to approach management of patients prior to stoma reversal and in preventing symptoms of LARS. In spite of only being set up in 2018, the pathway and clinics are already showing great success.